1973
DOI: 10.1177/000348947308200515
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Plasmacytomata of the Upper Respiratory Tract

Abstract: Extramedullary plasmacytomata may arise in any structure containing re-ticulo-endothelial tissue. Such tumors may be either isolated or the initial lesion of a generalized disseminated condition. Ideally, multiple involvement should be diagnosed at the presymptomatic stage; this may be possible by detecting variations in the immunoglobulins. Histologically, electron microscopy is advised to detect the plasma cell in the more undifferentiated case. Nine cases are reported. Two cases showed multiple involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

1975
1975
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 6 publications
3
21
0
2
Order By: Relevance
“…Clinically [3941], the plasmacytoma extraosseous is present as a sessile or pedunculated exophytic neoformation, circumscribed or infiltrative, ranging in color from red-purple to gray or yellow-white [42–50]. …”
Section: Classification and Related Aspects Of The Oral Pathologiementioning
confidence: 99%
“…Clinically [3941], the plasmacytoma extraosseous is present as a sessile or pedunculated exophytic neoformation, circumscribed or infiltrative, ranging in color from red-purple to gray or yellow-white [42–50]. …”
Section: Classification and Related Aspects Of The Oral Pathologiementioning
confidence: 99%
“…In two-thirds of cases in the head and neck, EMP is located in the upper respiratory tract or oral cavity primarily in the nose, sinuses and nasopharynx region 2. Solitary EMP of the parotid gland is a rare condition among all head and neck EMPs 4.…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary plasmacytoma (EMP) most frequently arises in the upper aerodigestive tract. Booth et al in their review of 250 reported cases stated that primary EMP usually affect the head and neck region 2. SP of the parotid gland is a rare condition with the first case reported in 1965 3.…”
Section: Introductionmentioning
confidence: 99%
“…EMP is a neoplasm of the plasma cells arising in areas other than bone and bone marrow without any systemic signs of underlying multiple myeloma. The majority of EMPs occurs in the head and neck with a marked predilection for the nasal cavity and paranasal sinuses [15][16][17][18][19]. They are non-disseminating but locally aggressive [18].…”
Section: Discussionmentioning
confidence: 99%